ZIF-Derived CuPt@Ag as Catalyst for Hydrogen Evolution Reaction - Yerlikaya, Gurbet; Koca, Mehmet Burak; Yazıcı, Birgül; Farsak, Murat; Kardaş, Gülfeza (Journal of Basic & Applied Sciences, 2021)
In this study, ZIF-Cu and ZIF-Pt were synthesized from 2-methyl imidazole with Cu and Pt salts in the methanol medium. The synthesized ZIFs were annealed to produce a CuPt nanocatalyst in the tube furnace. The Cu: Pt (3:1) nanocatalyst slurry was deposited on silver deposited carbon rod electrode (CE). The hydrogen evolution reaction (HER) activities for the catalyst were measured in a 1 M KOH solution by using potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques. The morphological structure and composition of CuPt@Ag have been studied by scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDX). It was observed that the prepared electrode surface had not only a homogeneous and porous structure but also nano-sized particles distributed on the surface. It has been observed that the current is increased from 5.22 mA cm-2 to 25.80 mA cm-2 under -1.55 V potential at CuPt@Ag electrode. The high current density shows that HER efficiency increases on the prepared catalyst.